Contribution to development of software system for the automated design gears - Novaković, Dragoljub; Gatalo, Ratko; Rekecki, Jožef; Navalušić, Slobodan (Journal of Production Engineering, 1989)
The results presented in this paper are a part of the software system for calculating and verifying stress and producing all the documentation for gears. The paper describes the starting design logic and methodology, which utilize optimal values of relevant factors to provide designers with all the elements necessary to define the gear. The calculated values enable the designer to create gears with the maximum degree of safety against bending, stress, and wear. Additionally, the software, based on these calculated values, designs and generates drawings for the gears. This paper specifically showcases the software for the first phase, which is the calculation and verification of gears with straight and helical teeth.